TRANSFORMING END OF LIFE CARE THROUGH CLINICAL TEMPLATE DESIGN AND TRAINING. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Faull, Christina; Prasad, Rish; Griffiths, Adam; Pearson, Wendy; Wong, Richard; Gray, Sarah-Jane; Feathers, Luke; Brown, Jayne
Abstract : National evidence suggests that whilst up to 67% patients wish to die in their own home, only 21% of patients actually do so. Recent Leicester City data reviewing emergency admissions and mortality suggests that recognising those patients who are not going to recover is inadequate in both primary and secondary care. Current systems and skills appear to be failing dying patients and their families, with local financial modelling also suggesting significant savings if appropriate care arrangements had been anticipated and implemented. To improve care for this vulnerable patient group, a local enhanced service (LES) was commissioned and an innovative three strand approach developed in conjunction with local providers and experts. Firstly, a clinical template for an Emergency Health Care Plan (EHCP) was created, using unique macros developed collaboratively with palliative care physicians, geriatricians and IT experts. This SystemOne template allows care plans for pre-defined conditions to be completed quickly and efficiently, providing outline plans for core clinical event scenarios which can be used to aid both completion and provide depth and breadth to the EHCP which is generated by the template. Secondly, locality mentors and practice end of life care champions were appointed with a training programme developed with the local Consultants in palliative medicine. Thirdly, extensive evaluation of the impact of the project on both patient and clinician needs, with baseline, peri- and end-point analysis planned and costed from the outset. This abstract seeks to demonstrate the collaborative work behind the template, and the benefits of its use to practising clinicians, as already evidenced by its recent expansion to neighbouring CCGs.